Correlation between Personal Hygiene and the Incidence of Pediculosis Capitis - Usi Lanita; Lativa Fauzani; Evy Wisudariani; Sri Astuti Siregar; Kasyani Kasyani (Lembaga Pengembangan Kinerja Dosen, 2023)
Pediculosis capitis (head lice) is a parasite that sucks blood and infests the human scalp. It often attacks children and spreads rapidly in crowded environments such as orphanages and boarding schools. The research aims to determine the relationship between personal hygiene and the incidence of pediculosis capitis. Method: quantitative research with a cross-sectional design. The population was 131 people, with a sample size of 85 respondents. The sampling technique uses purposive sampling. Data were analyzed univariately and bivariately using the chi-square test with a confidence level of 95%. Results: The results of the study showed that residents of the orphanage in Jelutung District, Jambi City (55.3%) experienced cases of pediculosis capitis, and 62.4%) had poor personal hygiene. There was a relationship between personal hygiene (p = 0.001) and the incidence of pediculosis capitis at the orphanage. Conclusion: There is a relationship between personal hygiene and pediculosis capitis. It is hoped that the residents of the orphanage will maintain and improve good and correct personal hygiene, and then health officers should routinely provide health education regarding personal hygiene and pediculosis capitis in the orphanage.